2022
DOI: 10.1111/hsc.14075
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health and social support from online communities during pregnancy*

Abstract: Childbearing is one of the most significant life events that bring not only joy but also anxiety and stress. The World Health Organisation (WHO, 2004) reported that worldwide about 10% of pregnant women and 13% of women who had just given birth experience a mental disorder, primarily depression. In developing countries this share was even higher, that is, 15.6% during pregnancy and 19.8% after childbirth. Moreover, perinatal depression and stress are also related to several adverse child outcomes (Aizer et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…10,12,13 The prior studies showed similar results with otolaryngologic OSCs being utilized by a predominately white, female, young to middle-aged, and highly educated audience and revealed similar positive psychosocial and knowledge benefits. 14,15 Our racial and gender demographics are comparable to prior literature on CRS with our cohort predominately identifying as white and female. It should be noted that minority groups, particularly Hispanic and African American patients, are likely underrepresented in CRS research and that we may not have an accurate demographic assessment of all CRS patients.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…10,12,13 The prior studies showed similar results with otolaryngologic OSCs being utilized by a predominately white, female, young to middle-aged, and highly educated audience and revealed similar positive psychosocial and knowledge benefits. 14,15 Our racial and gender demographics are comparable to prior literature on CRS with our cohort predominately identifying as white and female. It should be noted that minority groups, particularly Hispanic and African American patients, are likely underrepresented in CRS research and that we may not have an accurate demographic assessment of all CRS patients.…”
Section: Discussionsupporting
confidence: 73%
“…Prior studies have characterized the demographics and investigated the impact of OSCs on otolaryngologic diagnoses and treatments such as idiopathic subglottic stenosis, vestibular disorders, and bone‐anchored hearing aids but this has yet to be done in a CRS OSC 10,12,13 . The prior studies showed similar results with otolaryngologic OSCs being utilized by a predominately white, female, young to middle‐aged, and highly educated audience and revealed similar positive psychosocial and knowledge benefits 14,15 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation